2011
DOI: 10.2308/iace-10022
|View full text |Cite
|
Sign up to set email alerts
|

It's What's Outside that Counts: Do Extracurricular Experiences Affect the Cognitive Moral Development of Undergraduate Accounting Students?

Abstract: This study applies the psychological theories of Kohlberg (1969, 1979) and Rest (1986) and explores existing literature that investigates factors affecting the cognitive moral development of accountants (see Jones et al. [2003] for a review of this literature), while advancing discourse regarding the contributing factors of external classroom activities on the development of accounting students' moral growth. Using a sample of 396 undergraduate accounting students from across the United States, we examine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…These categories seem to include all the possible experiences that allow students to practice concrete activities interacting with the environment. Previous studies measured the involvement of students in different cultural activities by constructing an index score (Brown‐Liburd and Porco ; Rubin, Bommer, and Baldwin ). In our case, we measured the latent variable students' variety of cultural activities by a linear combination that summarizes the number of different activities the student was involved in, excluding political activities that are not carried out by the students in our sample.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These categories seem to include all the possible experiences that allow students to practice concrete activities interacting with the environment. Previous studies measured the involvement of students in different cultural activities by constructing an index score (Brown‐Liburd and Porco ; Rubin, Bommer, and Baldwin ). In our case, we measured the latent variable students' variety of cultural activities by a linear combination that summarizes the number of different activities the student was involved in, excluding political activities that are not carried out by the students in our sample.…”
Section: Methodsmentioning
confidence: 99%
“…Variety of Cultural Experience. The literature has defined different categories of cultural activities encompassing volunteer experiences and community service, political activities, active involvement in art/drama/music associations, and participation in clubs/fraternities (Brown-Liburd and Porco 2011;Roulin and Bangerter 2013;Rubin, Bommer, and Baldwin 2002). Students' participation in cultural activities was measured by asking the students to indicate whether they took part in the following activities: artistic, volunteering, political, and church groups.…”
Section: Variable Coding Proceduresmentioning
confidence: 99%
“…ECAs stand out for their ability to create spaces for the development of conflict resolution skills [44][45][46] and critical thinking and reflection on ethical values [12,14,47]. Indeed, Schripsema et al [13] concluded that students who participated in ECA had better reflective skills than those who were not involved in such activities.…”
Section: Eca (Extracurricular Activities) To Promote Reflective Learningmentioning
confidence: 99%
“…In the field of curriculum development, researchers have shown an increased interest in analyzing the concept of reflection in higher education [9] and in demonstrating the importance of reflective practice within the curriculum in order to develop attitudes that contribute to sustainable development [10,11]. With regard to research into extracurricular activities, recent evidence suggests the relevance of these activities in the improvement and development of reflective skills [12][13][14]. However, in-depth studies exploring students' experiences of self-reflection related to extracurricular activities (ECA onwards) are much needed [14].…”
Section: Introductionmentioning
confidence: 99%
“…One stream of research attributes accounting frauds to the failure of educators to implement adequate ethics training in accounting education programs (Brown-Liburd & Porco, 2011;Ferguson et al, 2011;Miller & Shawver, 2018). Some authors suggest that the education system should bear some of the responsibility for the apparent low moral standards of the accounting profession highlighting the need to re-examine the level and type of ethics education (McPhail, 1999;Shawver, 2009).…”
Section: Importance Of Ethics Educationmentioning
confidence: 99%